Evaluation of a daylight-responsive, iterative, closed-loop light control scheme. (April 2020) - Maiti, PK; Roy, B
In this paper an iterative, closed-loop light control scheme is proposed and evaluated by a white light emitting diode-based, daylight-responsive luminaire to follow the time-varying pattern of correlated colour temperature and illuminance of a daylight scene. The proposed control scheme functions primarily with the response signals of two RGB colour sensors, viz., a daylight sensor to monitor the daylight scene at the window plane and an internal light sensor to monitor the light scene created by the test white light emitting diode luminaire. The control scheme controls the lumen delivery of individual light emitting diode arrays of the test luminaire by adjusting the duty cycles to follow the instantaneous correlated colour temperature of daylight and at the same time to respond to the variation of window plane illuminance in the reverse pattern. Evaluation is conducted by laboratory testing and in situ testing. The maximum deviations in correlated colour temperature, illuminance and chromaticity from the required values under laboratory testing and in situ testing are found to be25 K, 0 . 7 lx, 0 . 0032 and84 K, 5 lx, 0 . 0032, respectively, which establish the acceptable performance of the proposed iterative light control scheme.